Ubezpieczenia społeczne a nabywanie prawa do świadczeń w zjednoczonej Europie - Gubernat, Ewa (Wydawnictwo Akademii Ekonomicznej im. Oskara Langego we Wrocławiu, 2008)
The process of continuous relocation of the population is one of the basic problems of socialpolitics of member states of United Europe at the threshold of the 21st century. Economic factors aswell as non-economic (social and cultural) are reasons for mass migration. Among them the mostimportant are as follows: the money chase, development of international corporations, the concept ofa global village, high tax loads in the home country, increase in national minorities population due towars in the third world countries, bonds of blood etc. Therefore, each member state should respect notonly domestic social security regulations but also international agreements concerning rights of immigrantsto social security benefits. (original abstract)
Prace Naukowe Akademii Ekonomicznej we Wrocławiu. Ekonomia i Międzynarodowe Stosunki Gospodarcze (16); 2008; nr 1193, s. 111-120